Flexible organic light-emitting diodes for antimicrobial photodynamic therapy - Cheng Lian (Nature Portfolio, 2019)
OLED is ready for photodynamic therapy Flexible OLED technology is becoming increasingly mature and is ready to open new directions in antimicrobial photodynamic therapy. An international team led by Prof Ifor Samuel from University of St Andrews, UK presents a comprehensive study to show that flexible organic light-emitting diodes (OLEDs) are ideal light sources to be used in photodynamic therapy to kill bacteria. They design the OLED device structure to enable large area, high uniformity, low driving voltage, long operational lifetime, adequate shelf-life and colour tunability and address all the requirements of photodynamic therapy. Actual biological experiments show killing rates of more than 99% for S. aureus bacteria. The approach clearly demonstrates the huge potential of OLEDs for treatment of bacterial infections and future wearable healthcare devices.